HIV-induced membraneless organelles orchestrate post-nuclear entry steps. (31st October 2022) - Scoca, Viviana; Morin, Renaud; Collard, Maxence; Tinevez, Jean-Yves; Di Nunzio, Francesca
ABSTRACT: HIV integration occurs in chromatin sites that favor the release of high levels of viral progeny; alternatively, the virus is also able to discreetly coexist with the host. The viral infection perturbs the cellular environment inducing the remodelling of the nuclear landscape. Indeed, HIV-1 triggers the nuclear clustering of the host factor CPSF6, but the underlying mechanism is poorly understood. Our data indicate that HIV usurps a recently discovered biological phenomenon, called liquid–liquid phase separation, to hijack the host cell. We observed CPSF6 clusters as part of HIV-induced membraneless organelles (HIV-1 MLOs) in macrophages, one of the main HIV target cell types. We describe that HIV-1 MLOs follow phase-separation rules and represent functional biomolecular condensates. We highlight HIV-1 MLOs as hubs of nuclear reverse transcription, while the double-stranded viral DNA, once formed, rapidly migrates outside these structures. Transcription-competent proviruses localize outside but near HIV-1 MLOs in LEDGF-abundant regions, known to be active chromatin sites. Therefore, HIV-1 MLOs orchestrate viral events prior to the integration step and create a favorable environment for the viral replication. This study uncovers single functional host–viral complexes in their nuclear landscape, which is markedly restructured by HIV-1.